The Role of Research Institutions in Civic Science & Sustainable Development Diplomacy - Okner, T (2015)
Civic science, citizen science, participatory science...the increasing popularity of these terms heralds a more pluralistic, multi-stakeholder process to inform policy-making. This paper investigates the theories behind civic science and presents its relationship to sustainability, and to climate change in particular. It examines how a shift in the science-politics interface impacts research organizations and, more specifically, examines the role of research organizations in sustainable development diplomacy. The Global Alliance for Climate Smart Agriculture, newly launched after several years of incubation, is put forth as a case study on sustainable development diplomacy. CGIAR, a consortium of fifteen research centers, herein represents the research community at large. The role of research institutions in the formation and future of the GACSA is considered through a qualitative, interviews-based, assessment. Interviews with 26 representatives from six distinct stakeholder groups focused on CGIAR's influential leadership role, grappling with civic science, in the development of the GACSA.